Pendekatan MDA Framework Pada Pengembangan Permainan Baby Care Augmented Reality dengan Outfit Marker - Pradhana Hafiizh Bachtiar; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Simulation games are popular game genres that have been used frequently in the early days platform of the first generation of playstation consoles. But remember at the moment the simulation game is limited to 2D content, so it needs to be developed further with a more interactive concept by using 3D graphics that serves to visualize the character object contained in the marker and then combined using Augmented Reality technology. A simulation game containing baby care needs to be developed to continue the animal themed simulation game so as to provide an element of variation in the simulation game genre. Therefore it is necessary to develop a simulation game by combining augmented reality baby care technology developed on Android mobile platform based on MDA framework. Methods applied to the development of this game using the Iterative with Rapid Prototyping (IRP) method. On this method the begining of the game creation comes from respondents who understand about the game or play tester that uses prototype paper with repetition techniques until the game concept really satisfy and is considered appropriate by the respondents. Then game testing using black box and playtesting method. On a playtesting method involving ten respondents who were not involved in game creation. After which the results obtained that this game has an interesting concept and has been in accordance with the needs analysis to simulate infant care into the form of a more interactive treatment.